PARALLEL FRAMEWORK OF MUḤAMMAD AND MOSES'S STORY: AN ANALYSIS OF THE NARRATIVES OF ḤALĪMAH AL-SAʿDIYYAH - Ahmad Sanusi Azmi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2018)
Kajian modern tentang asal-usul sīrah Nabawiyah telah menelusuri dan menemukan keberadaan pengaruh kitab suci sebelumnya dan unsur-unsurnya dalam narasi sīrah. Kisah tentang Halimah, sang ibu susuan, menurut Raven, menunjukkan kejadian paralel dengan kematangan Yesus ketika bayi, dalam Injil. Selain itu, para sarjana Muslim seperti Ibn Hisham ditemukan konsisten dalam membuat perbandingan paralel antara Muhammad dan Musa dalam karyanya. Tulisan ini memfokuskan pada kehidupan awal yang terfokus pada periode Ḥalīmah al-Sa'diyyah dengan menganalisis penggunaan referensi Al-Quran dalam narasi. Penelitian ini bersifat kualitatif dengan metode pendekatan kritis dan analisis tekstual untuk membaca cerita. Kajian ini menemukan proposisi bahwa ada dua kemungkinan alasan yang mengarahkan Ibn Hisham menambahkan ayat 28:12 dari Al-Qur'an sebagai referensi atas catatan waktu Muhammad sebagai bayi yang menyusu. Isu pertama ketidakjelasan digital dalam narasi Ibn Isāq. Dan yang kedua adalah memberikan kepercayaan kepada kisah kedua nabi, Muhammad dan Musa.Modern studies of the origin of sīrah nabawiyyah have traced and suggested the existence of influence of previous scriptures and their elements within the sīrah narrative. The extraordinary speed and marks of physical maturity in Prophet Muḥammad’s wet-nurse period with Halimah, which, according to Raven, indicates a parallel occurrence with Jesus' precocity in the Gospels of the Infancy. Besides, Muslim scholars such as Ibn Hishām was found to consistently make parallel comparison between Muḥammad and Moses in his work. This study aims to explore the narratives of Prophet Muḥammad’s early life, with special focus to his period with Ḥalīmah al-Sa’diyyah and analyse the use of Quranic reference in the narrative. The study is qualitative in nature in which the researcher employed critical and textual analysis to examine the story. The present study in its finding proposes that there are two possible reasons which lead Ibn Hishām to adduce verse 28:12 of the Quran as his reference to the account of Muḥammad’s time as a suckling infant. The first is to elucidate lexical obscurity in the narration of Ibn Isḥāq. And the second is to give credence to the similarity between the accounts of two prophets, Muḥammad and Moses.